TLR2-Melatonin Feedback Loop Regulates the Activation of NLRP3 Inflammasome in Murine Allergic Airway Inflammation - Wu, Hui-Mei; Zhao, Cui-Cui; Xie, Qiu-Meng; Xu, Juan; Fei, Guang-He (Frontiers in Immunology, 2020)
Toll-like receptor 2 (TLR2) is suggested to initiate the activation of NLRP3 inflammasome, and considered to be involved in asthma. The findings that melatonin modulates TLRs-mediated immune responses, together with the suppressing effect of TLRs on endogenous melatonin synthesis, support the possibility that a feedback loop exists between TLRs system and endogenous melatonin synthesis. To determine whether TLR2-melatonin feedback loop exists in allergic airway disease and regulates NLRP3 inflammasome activity, wild-type (WT) and TLR2-/- mice were challenged with OVA to establish allergic airway disease model. Following OVA challenge, WT mice exhibited increased-expression of TLR2, activation of NLRP3 inflammasome and marked airway inflammation, which were all effectively inhibited in the TLR2-/- mice, indicating that TLR2-NLRP3 mediated airway inflammation. Meanwhile, melatonin biosynthesis was reduced in OVA-challenged WT mice, while such reduction was notably rescued by TLR2 deficiency, suggesting that TLR2-NLRP3-mediated allergic airway inflammation was associated with decreased endogenous melatonin biosynthesis. Furthermore, addition of melatonin to OVA-challenged WT mice pronouncedly ameliorated airway inflammation, decreased TLR2 expression and NLRP3 inflammasome activation, further implying that melatonin in turn inhibited airway inflammation via suppressing TLR2-NLRP3 signal. Most interestingly, although melatonin receptor antagonist luzindole significantly reduced the protein expressions of ASMT, AANAT and subsequent level of melatonin in OVA-challenged TLR2-/- mice, it exhibited null effect on leukocytes infiltration, Th2-cytokines production and NLRP3 activity. These results indicate that a TLR2-melatonin feedback loop regulates NLRP3 inflammasome activity in allergic airway inflammation, and melatonin may be a promising therapeutic medicine for airway inflammatory diseases such as asthma.